2018
DOI: 10.1590/1980-5373-mr-2017-0836
|View full text |Cite
|
Sign up to set email alerts
|

Sputtering Power Induced Physical Property Variation of Nickel Oxide Films by Radio Frequency Magnetron Sputtering

Abstract: NiO thin films were deposited on Si and Corning 1737 glass substrates using radio frequency (rf) magnetron sputtering system. The physical properties of NiO films under different sputtering power were thoroughly studied. The XRD results indicated that as-prepared NiO films with the sputtering power above 100 W developed only (200) preferred orientation. The AFM results showed that the NiO films were composed of different-size NiO nano-grains and the grain size increased with increasing the sputtering power. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The value of Ra may be affected by the 100-W RF power condition, and the axis of the sputtering target of 45 o as thin film deposited with perpendicular axis generates smoother roughness (< 1 nm) [14]. Smooth roughness of the surface can be achieved by adjusting power lower than 100 W, as mentioned by other researchers [24]. In chemical synthesis growth mechanism, uniform and regular shape in the form of nanorod developed [13].…”
Section: Thin Film Characteristicsmentioning
confidence: 84%
“…The value of Ra may be affected by the 100-W RF power condition, and the axis of the sputtering target of 45 o as thin film deposited with perpendicular axis generates smoother roughness (< 1 nm) [14]. Smooth roughness of the surface can be achieved by adjusting power lower than 100 W, as mentioned by other researchers [24]. In chemical synthesis growth mechanism, uniform and regular shape in the form of nanorod developed [13].…”
Section: Thin Film Characteristicsmentioning
confidence: 84%
“…The higher RF power in the sputtering process induces the bombarding argon ions with higher kinetic energy, which increases the sputtering yield. [9,28] Increasing the RF power resulted in a higher deposition rate and altered the optical properties of the films as it has been reported in literatures [9,[34][35][36][37][38]. The optical transmission was influenced both by the roughness and thickness of the films.…”
Section: Optical Transmissionmentioning
confidence: 91%
“…The optical transmission was influenced both by the roughness and thickness of the films. Several groups demonstrated that the optical transmission of the films decreased with higher roughness and thickness [9,34,35,38] due to high energy of sputtering particles as the RF power increased [32,39].…”
Section: Optical Transmissionmentioning
confidence: 99%
“…12 The metal chloride has different uses like industrial to product oxides and ferrites. 13 NiO samples have been fabricated using various kinds of techniques, including thermal evaporation, 14 plasma enhanced chemical vapor deposition, 15 sol-gel, 16 sputtering, 17 RF magnetron sputtering, 18 and spray pyrolysis. 19 In this work, the effect of Cu doping ratio with the NiO thin film characterized by means of focusing on structural, optical properties, and electrical has been studied.…”
Section: Introductionmentioning
confidence: 99%